How Corporate Social Responsibility Boosts Corporate Financial and Non-financial Performance: The Moderating Role of Ethical Leadership - Bouichou, Said Id; Wang, Lei; Zulfiqar, Salman (Frontiers in Psychology, 2022)
Corporate social responsibility has always been considered an important topic, and many studies discussed the association between CSR and corporate performance, but the results are still inconclusive. This study is to examine the impact of CSR on corporate performance (financial and non-financial) with the moderating impact of ethical leadership. Data is gathered from 222 companies in Morocco using a simple random sampling technique. Moreover, for measuring stomer satisfaction and corporate image in the kinds of customers towards CSR activities of the firms, we collected data from customers and got 209 responses. For analyzing the results of this study, structural equation modeling has been used, while for moderation, the hierarchical regression technique has been adopted. Findings revealed a significant positive association found between CSR and corporate finance as well as non-financial performance (corporate image and customer satisfaction). Ethical leadership helps in increasing financial and non-financial performance of organization. The findings further revealed that ethical leadership moderates the relationship between CSR and firm financial and non-financial (corporate image and customer satisfaction) performance. This study will assist management in realizing the importance and implementation of CSR practices in organizations, especially in the Moroccan context.